A case of cholangiolocellular carcinoma featuring intratumoral hepatic artery penetration: A case report. (2017) - Yamane, Hiroaki; Abe, Tomoyuki; Amano, Hironobu; Kobayashi, Tsuyoshi; Hanada, Keiji; Yonehara, Shuji; Ohdan, Hideki; Nakahara, Masahiro; Noriyuki, Toshio
Highlights: Cholangiolocellular carcinoma (CoCC) is a rare type of liver cancer. We report a 79-year-old woman with CoCC detected following elevated C19-9 levels. Uniquely, the hepatic artery was observed penetrating the >60 mm tumor on imaging. Recurrence with multiple liver metastases occurred 6 months after surgery. Tumor size and/or this unique growth pattern may be risk factors for recurrence. Abstract: Introduction: Cholangiolocellular carcinoma (CoCC) is thought to originate from hepatic stem cells. Its clinical characteristics, including radiological and prognostic factors, remain unclear. Presentation of case: A 79-year-old woman with hypertension was admitted to our hospital after abnormal tumor marker levels were detected during an annual physical examination. Her laboratory data results were within normal range, and she was classified as Child-Pugh A. Enhanced computed tomography revealed a tumor located on the left side of the liver, with a maximum size of 60 mm. The tumor showed heterogeneously enhancing edges in the arterial phase, while prolonged tumor enhancement was detected in the delayed phase. Tumor penetration by the left hepatic artery was evident, whereas the left portal vein was invaded by the tumor. The preoperative diagnosis was cholangiocellular carcinoma. Left hepatectomy and cholecystectomy were performed with no postoperative complications; the final diagnosis was CoCC. Multiple liver metastases appeared 6 months after surgery; the patient is now receiving systematic chemotherapy. Discussion: While portal vein penetration into CoCCs has been reported, the same is not true of the hepatic artery; therefore, this case illustrates a unique tumor growth pattern. Conclusion: A unique growth pattern as well as a large primary tumor may contribute to earlier recurrence.